EGRA Technique to Improve Students Ability in Using Simple Past Tense - Mohammad Fatoni; Hasty Audytra; Lina Ardiyanti (EDUTEC : Journal of Education And Technology, 2018)
The objective of this research was find out whether or not the use of EGRA (Experience, Generalization, Reinforcement, Application) technique was able to improve students ability in using simple past tense of the third grade students of MTs Terpadu Manba’ul Ulum Sukosewu. It was experimental research. The resulf of the data indicated that, there was difference between the value of students pre-test and post-test. The finding of this research was the use of EGRA (Experience, Generalization, Reinforcement, Application) Technique were effective in teaching grammar efficient and had good improvement the students grammar ability in using simple past tense of MTs Terpadu Manba’ul Ulum Sukosewu.